Legislative Learning : the 104th Republican Freshmen in the House. - Barnett, Timothy J. (Garland reference library of social science., 1999)
Based upon freshmen class surveys and interviews, this book seeks to understand the 104th GOP freshmen's high class identity and group power as well as the nature and scope of the class's legislative learning.